(untitled) (AGROINNOVATSIYА, 2024)
The factors affecting the growth, development, coverage of the consumed food with the unit of product, characteristics of the formation of meat productivity, its weight and quality of bulls of different genotypes obtained as a result of Holsteining were determined.